From Fighting to Flying: Women Leadership in Private Schools of Kathmandu Valley - Subedi, Ramila; Shrestha, Milan (KMC Journal, 2023)
This article unveils the stories of women who have been standing as leaders in private schools of Kathmandu Valley. The purpose of the study was to uncover how women leaders faced challenges on their leadership journey, and how they coped with those challenges. Interpretivism was adopted as the research paradigm using narrative research design. Three women leaders from private schools of Kathmandu Valley were selected purposively and the open-ended questions were used to assemble their narratives. The narratives of the women were unfolded through our engagement in the process of storytelling and reflection. The study unveiled that the women, who appear to be sophistically handling leadership positions in their particular organizations, are hovered around by different challenges. Moreover, their stories present the challenges they have gone through so as to reach where they are; and how they have applied mechanisms to cope with the challenges that appeared on their way. The challenges on the women’s way, as suggested by their stories, were connected to the discourse of gender while they had utilized their willpower and passion, professional integrity and altruism as mechanisms to cope with the challenges. Nonetheless, the study even hints that some challenges are tough to be bounced back since they are deeply rooted to social mentalities.